Low protein diet supplemented with ketoacids on muscle wasting in chronic kidney disease: A clinical trial - Zhang, Yueyue; Gu, Lijie; Wang, Ling; Rong, Shu; Yuan, Weijie (Frontiers in Medicine, 2022)
Aim: Nutrition is an important part of the care of chronic kidney disease (CKD) patients. However, there are limited clinical researches in CKD patients’ skeletal muscle nutrition. We carried out this study to find out whether low-protein diet supplemented with ketoacids (LPD+KA) could improve muscle wasting in CKD patients. Methods: Patients were enrolled in this non- blind, parallel- group, randomized trial assessing the nutritional status in CKD, randomly assigned to either LPD+KA group or conventional LPD group. Blood samples such as Hemoglobin, Cystatin C, Creatinine, BUN, Albumin, Pre- Albumin, Glycerin Trilaurate, Cholesterol were measured at baseline and every 3 months. The parameters of skeletal muscle and other body composition were assessed before and after dietary intervention for 12 months. Results: A total of 58 CKD patients completed the study and were available for further analysis. The hemoglobin and albumin were observed to be markedly improved in LPD+KA group during the follow up as compared to baseline. Body mass index and total body water index of both groups were increased upon follow but the increase in LPD+KA group was comparatively higher. Moreover, increase in body fat %, skeletal muscle mass index and appendicular skeletal muscle mass index was observed in both groups between baseline and follow up, but it was statistically insignificant. Conclusion: This study did not find a significant improvement of KAs on muscle wasting, and a longer time or more indices study may need to find the effects of the LPD+KA diets.